Non-functional pituitary carcinoma - He, Haiyong; Guo, Ying; Li, Manting; Luo, Lun; Bhattarai, Robin; Li, Wensheng (Nepal Journal of Neuroscience, 2021)
We present as case to review and present the clinical features, diagnosis and treatment of non-functional pituitary carcinoma (NFPC).We operated on a case of NFPC. After surgery, gamma knife therapy, temozolomide chemotherapy and whole craniospinal irradiation, the patient still had poor tumor control and died 7 months after operation.FPC is very rare. It needs to be diagnosed with a combination of clinical suspicion, imaging and dynamic monitoring. It is necessary to find more effective methods to control the progress of tumor while routine treatment fails.